Pemeriksaan Kesehatan Tekanan Darah Di Kantor Kelurahan Biraeng Kecamatan Minasatene Kabupaten Pangkep - Nurhaedah, Nurhaedah; Sutarna, Agus; Abdullah, Dahlan; Haedir, Haedir; Aditia, Donny; Zafera Adam, Jeanne d'Arc; Erliana, Cut Ita (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Blood pressure is the power needed so that blood can flow in the blood vessels and circulate to all tissues of the human body. Blood smoothly circulates to all parts of the body functioning as a medium for transporting oxygen and other substances needed for the life of cells in the body. The purpose of this activity is to provide basic health information to the public regarding physical examinations, blood pressure, as well as provide counseling based on the results of health checks so that a healthy society is created and to find out the average community blood pressure. So that if you find results that are not within normal limits, you can immediately be given education to regulate your lifestyle and are advised to consult the nearest doctor. If we can find out abnormal processes in the body as soon as possible then complications from the disease can be avoided as early as possible and for the implementation of PKM activities carried out at the Biraeng Village Office, Minasatene District, Pangkep Regency which will be held in May 2023.